A MONOGENIC TREMATODE (DACTYLOGYRUS SP.) ASSOCIATED WITH HYBRID TILAPIA (OREOCHROMIS NILOTICUS X O. AUREUS) MORTALITY - AL-HARBI, AHMED H. (The Bioscan, 2011)
During a routine monitoring programme of Wadi Hanifah stream, some of the hybrid tilapia (Oreochromis niloticus x O. aureus) was found dead in the stream water. The occurrence of a disease in hybrid tilapia in Wadi Hanifah stream is described. Mortalities of tilapia are considered to have been caused by heavy infections of a monogenic trematode (Dactylogyrus sp.). Moribund fish were dark in color, weak, swimming alone and have taken shelter in the marginal areas and moved very slowly when disturbed. It was found that the parasites were localized in the gills only. No exotic parasites were observed in guppy (Poecilia reticulate) molly, (P. latipinna), platy (Xiphophorus maculates) and Pteroplichthys sp.